No-take marine reserves boost the resilience of commercial fish from the catastrophic effects of a volcanic eruption - José Carlos Hernández; José Carlos Mendoza; Jesús M. Falcón; Sabrina Clemente; Pelayo Salinas; Natalí Denis-Lazzari; Carlos Sangil; Marc Balsalobre; David Martínez; Bernat Hereu; Alberto Brito (PLoS ONE, 2026)
Submarine volcanic eruptions are strong pulse disturbances that can cause abrupt mortality and long-lasting changes in marine communities. In October 2011, a submarine eruption off El Hierro (Canary Islands, Spain) generated a sulphurous plume that affected the Punta de La Restinga–Mar de Las Calmas Marine Reserve and surrounding coastal areas. Using a 25-year time series of fish community data, we assessed post-disturbance trajectories of commercial species across different protection levels within the impacted region. Resilience was analyzed as a sequential process, partitioned into resistance (initial biomass loss), recovery trajectory (temporal trend after the disturbance), and relative recovery compared with pre-eruption conditions. Because all sites were affected by the volcanic plume, our inference is restricted to comparative differences among protection categories rather than to the absolute effectiveness of protection. The no-take zone showed higher relative resistance and faster positive trajectories in total fish biomass than less-protected areas, indicating more favorable post-disturbance dynamics. However, eight years after the eruption, community structure had not fully returned to pre-eruption conditions in any protection level, reflecting contrasting recovery times among species with different life histories. Fast-growing species such as the parrotfish Sparisoma cretense recovered rapidly, whereas long-lived predators such as Epinephelus marginatus remained below their pre-disturbance biomass. Our results provide a long-term, community-level comparison of post-volcanic recovery within a marine reserve and highlight how protection status is associated with differences in recovery dynamics under a rare natural disturbance.